Analysis of Current ICT Technologies in Education and Their Comparisons with the Proposed Technologies - Boyraz, Armağan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In its general sense education is a form of learning in which the knowledge, skills, and habits of a group of people are transferred from one generation to the next through teaching, training, or research. Education frequently takes place under the guidance of others, but it can be autodidactic. It stands for information and communication technologies and according to the purpose of primer, it is described as information, creating contact, storing and disseminating the diverse array of the technological tools and resources used to manage. Among these technologies; there are computer, internet, broadcasting technologies (radio and television) and phone. On the other hand, networked computers and the internet are the ICTs that enable the best interactive and collaborative learning; their full potential as educational tools will remain unrealized if they are used merely for presentation or demonstration. Technology has become an important part of our daily life so that ICT in education has become indispensable. In addition, advanced Information Technology has gained much importance. Moreover, with developing technology, variations have been taking place in many fields such as industry, trade, health and education as well and the scope of information, access speed to information and access methods are rapidly changing. Educational institutions stand in the very middle period of change as we may refer to as information age. Within this period, the quite important missions fall particularly to the school administrators and teachers. Merely to educate literate individuals is not sufficient anymore, but technologically literate individuals should also be trained. The rapid development of ICT is leading to the establishment of what has been called the information society. New technologies have affected economical, social and educational structure of the society. Therefore, societies should follow technological changes. The most important condition to realize this matter is to integrate technology to the educational environment effectively. The study is designed as a case study with a mixed methods approach. The research group was composed of 522 students, 92 teachers and 11 school administrators, total of 625 participants. Data was collected from the participants with the help of a questionnaire. Findings indicate that technology is a current knowledge on the use of Information Technology. Due to technological advancements, automation has been achieved in our daily life, enabling educators to save time and the produce more accurate solutions to the problems. Students also benefited from the education serviced to them through Information Technology within the same period of time. The findings also have implications for the use of Information Technology, technological applications, ICT technologies, technological literacy, integration of technology and educational technology. Keywords: Technological Applications, ICT Technologies, Technological Literacy, Integrate Technology.

ÖZ: Teknoloji kullanımı, öğrenmenin gerçekleşmesi sırasında eğitim deneyimi kalitesinin artırılmasında önemli bir rol oynamaktadır. Eğitim teknolojisi kullanımı eğitimin çehresini değiştirmekte ve daha fazla fırsat yaratmaktadır. Öğrenciler, sınıf ortamlarına teknolojinin girmesiyle daha fazla bir ilgiyle öğrenmeye karşı daha ilgili olmaya başlamışlardır. Bu çalışmanın amacı, eğitimde güncel bilgi ve iletişim teknolojilerini önerilen teknolojilerle karşılaştırmak ve analiz etmektir. Çalışma karma yöntemli bir durum çalışması olarak tasarlanmıştır. Çalışmanın araştırma grubu 522 öğrenci, 92 öğretmen ve 11 okul yöneticisi olmak üzere toplam 625 kişiden oluşturulmuştur. Veriler, öğrencilerden, öğretmenlerden ve okul yöneticilerinden anket yöntemi ile toplanmıştır. Elde edilen bulgular teknoloji kullanımının öğrencilerin, öğretmenlerin ve okul yöneticilerin güncel bilgi ve iletişim teknolojileri üzerinde büyük bir etkisinin olduğunu göstermektedir. Eğitimdeki teknolojik gelişim sayesinde, günlük hayatımızda otomasyon sağlanmış ve bu sayede eğitimciler zaman kazanmış, daha kesin, doğru çözümler üretmiş, sınıf içerisindeki tüm öğrenciler de, aynı zaman dilimi içerisinde eğitilmiş ve daha güncel ve kaliteli bir eğitim servisi elde etmişlerdir. Sonuçlar aynı zamanda teknoloji kullanımı, teknolojik uygulamaları, değişim dönemini, teknolojik okuryazarlığı, entegrasyon dönemini ve eğitim teknolojisini yansıtmaktadır. Anahtar Kelimeler: Teknolojik Uygulamalar, Değişim Dönemi, Teknolojik Okuryazarlık, Entegrasyon Dönemi.
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer and Instructional Technology Teacher Education, 2016. Supervisor: Dr. Hasan Oylum.
Keywords: Computer and Instructional Technology Teacher Education; Information and Communication Technologies in Education; Education - Computer network resources; Distance Education; Educational Technology; Teaching - Computer network resources; Technological Applications; ICT Technologies; Technological Literacy; Integrate Technology